Distinct psychological mechanisms for explicit and implicit aggression: evidence from the narcissism and sense of power - Hu, Qi; Meng, Zijun; Lu, Jiantao; Zhu, Yu; Zhang, Kaihua; Zhang, Qian (Frontiers in Psychology, 2025)
IntroductionAggression has been demonstrated a distinction between explicit and implicit social cognition. Explicit aggression refers to the conscious tendency to display aggressive behavior while maintaining necessary self-control. Implicit aggression is an unconscious aggressive behavior shaped by past experiences that operates beyond an individual’s control. Although aggression comprises explicit and implicit structures, the psychological mechanisms of such dual aggression remain unclear. According to the general aggression model, when individuals are unable to balance the internal state (e.g., narcissism and power), aggression may occur. Therefore, the current study explored the psychological mechanisms of the dual aggression by using narcissism and power.MethodsStudy 1 recruited 331 undergraduate students to complete online questionnaires assessing overt and covert narcissism, sense of power, and explicit aggression. A mediation model was constructed to examine the relationship among these variables. Furthermore, Study 2 assessed implicit aggression using the Implicit Association Test (IAT) to examine the relationship among narcissism, sense of power, and implicit aggression.ResultsThe results indicated that (1) covert narcissism was positively associated with explicit aggression, which was partially mediated by sense of power; (2) overt narcissism was positively correlated with explicit aggression, which was not mediated by sense of power; (3) overt and covert narcissism were positively associated with implicit aggression, whereas sense of power was not significantly correlated with implicit aggression; (4) there was no correlation between explicit aggression and implicit aggression.DiscussionThese findings offer valuable insights into the distinct psychological mechanisms underlying the explicit and implicit aggression, as suggested that their predictors were distinct. Covert narcissism may interact with other factors (e.g., sensitivity and hostility) to activate sense of power, thereby eliciting explicit aggression. Whereas individuals with higher overt and covert narcissism showed stronger implicit aggression.